2017
DOI: 10.3390/agriculture7110091
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Chemistry of Pesticides in Soil and Water

Abstract: Soils are the ultimate examples of physically and chemically irregular mixtures. They are also dynamic. Early investigators consequently did not understand the physical chemistry of pesticides in soil and water. By taking shortcuts instead of trying to understand the physical chemistry, they measured the wrong variables, used the wrong units, calculated the wrong parameters, and totally ignored chemical stoichiometry. Theoretical concepts for the physical chemistry of pesticides in soil have been published dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Chemically speaking they are classified as organophosphorus, organocarbamics (carbamates), and organochlorine compounds. Pesticides may create environmental problems with water and soil contamination (Gamble, ; Sepehri & Sarrafzadeh, ). In China, Ni, Cao, Ji, and Zeng () found that the concentration of organochlorine compounds in soil samples ranged from nondetected to 149 ng/g.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically speaking they are classified as organophosphorus, organocarbamics (carbamates), and organochlorine compounds. Pesticides may create environmental problems with water and soil contamination (Gamble, ; Sepehri & Sarrafzadeh, ). In China, Ni, Cao, Ji, and Zeng () found that the concentration of organochlorine compounds in soil samples ranged from nondetected to 149 ng/g.…”
Section: Introductionmentioning
confidence: 99%